A New Sphingolipid from the Sponge Iotrochota Baculifera of the Indian Ocean - Muralidhar, P.; Venkata Rao, D. (Asian Journal of Chemistry, 2010)
A new sphingolipid was isolated from the ethyl acetate solubles of the alcoholic extract of the sponge Iotrochota baculifera. The compound was characterized as (2S, 3S, 4R)-2-[(2’R, 4’E)-2’-hydroxy-4’-tetracosenoylamino]-1,3,4-trihydroxyoctadecane (1) by means of NMR and FABMS data.